Prognostic value of B7-H3 expression in metastatic renal cell carcinoma and its impact on immunotherapy response - Faruk Recep Özalp; Kutsal Yörükoğlu; Eda Çalışkan Yıldırım; Mehmet Uzun; Hüseyin Salih Semiz (BMC Cancer)
Abstract Background Renal cell carcinoma (RCC) is characterised by its immunogenic and proangiogenic nature and its resistance to conventional therapies. The advent of immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) has significantly improved patient survival, but resistance to these treatments remains a challenge. B7-H3, a potential immune checkpoint, has been implicated in modulating the tumour microenvironment and immune escape mechanisms in RCC. Methods Immunohistochemical analysis of B7-H3 expression was performed in 84 metastatic RCC patients. Tissue microarrays and separate sections of formalin-fixed paraffin-embedded tissue were used for immunohistochemical staining. Membranous staining of the tumor cells was scored and statistical analyses were performed to assess the correlation between B7-H3 expression and treatment outcome. Results B7-H3 expression was absent in 31% of patients, while 33.3% had a score of 1+, 31% had 2+, and 4.8% had 3+. High B7-H3 expression correlated with poorer OS (20 months vs. 45 months, p = 0.012). In patients receiving nivolumab, those with high B7-H3 expression had shorter PFS (2 months vs. 8 months, p = 0.037) and OS (17 months vs. 51 months, p = 0.01). B7-H3 expression was the only factor significantly affecting PFS and OS in multivariate analysis. Conclusion High B7-H3 expression is associated with poorer survival outcomes and reduced response to nivolumab in metastatic RCC patients. B7-H3 may serve as a predictive biomarker for immunotherapy response. Future studies should explore targeting B7-H3 in combination with existing therapies to enhance treatment efficacy.